Sistem Monitoring Suhu Dan Kelembaban Pada Budidaya Jamur Tiram Menggunakan ESP32 - Ridho’i, Achmad; Setyadjit, Kukuh; Era Yordhan, Bayu (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2023)
In order to get a good yield of oyster mushrooms, oyster mushroom farmers need to have good and correct knowledge of oyster mushroom cultivation, from seeding methods, mushroom fertilization, to maintenance of room conditions for oyster mushroom cultivation, farmers also need to maintain a room temperature of 28oC and 60% humidity. RH. In this final project, a tool is designed that can make it easier for oyster mushroom cultivators in places where oyster mushrooms are not supposed to be cultivated, such as in the city of Sidoarjo or anywhere that has hot weather, a temperature of 28oC and humidity of 60% RH is needed to produce maximum yields. . This tool is designed with a DHT 22 sensor which functions as a temperature and humidity detector for oyster mushroom cultivation which will later send a digital signal to the ESP32 microcontroller to process display data in the blink application, to provide command processes through the blynk application to turn on the exhaust and water pump. With this research, through the integration of monitoring the blynk application, the ESP32 microcontroller, Exhaust, and water pump can be useful for field users. This tool can help mushroom farmers remotely monitor and control temperature and humidity in hot cities.